Identification of affluent households in Poland by the structure of consumption expenditures - Wołoszyn, Andrzej; Głowicka-Wołoszyn, Romana (Economic and Environmental Studies, 2020)
The aim of the article was an attempt at identifying various levels of affluence of Polish households by their consumption structure as well as description of the volume, structure, and disparities in expenditures of the identified classes of affluence. A two-step procedure was conducted to determine relative affluence lines of 150%, 230%, and 450% of the median expenditures defining three classes labelled as affluent, wealthy, and rich. Comprising respectively 16%, 6%, and 1% of the population, these classes showed very diverse consumption structure.